ANALYSIS OF POTENTIAL DEVELOPMENT OF DAIRY CATTLE AGRIBUSSINESS AND RELATED PRODUCTION FACTOR WITH MILK PRODUCTION IN SEMARANG - Wahyu Imam Santoso; Mukson Mukson; Agus Setiadi (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
This study aims to analyze the development potential of dairy cows and the relationship of social, economic, and technical factors with milk production in the city of Semarang. The research was conducted by survey method. Two districts with the highest dairy cattle population were selected to determine the location, namely Gunungpati and Mijen Districts. Sampling was carried out by simple random sampling of 65 farmers. The data obtained were analyzed using Location Quotient (LQ) and Dynamic Location Quotient (DLQ) methods to see the potential for dairy cattle development. Spearman rank correlation analysis was used to determine the relationship between social, economic, and technical factors (age of breeder, the experience of raising livestock, education level, number of lactating cows, the month of lactation, forage feed, and concentrate feed) to milk production. The results showed that the Districts of Gunungpati and Mijen had LQ values of 1.649 and 0.926, respectively, and DLQs of 1.0329 and 1.0327. It can be interpreted that Gunungpati District is the base area and the criteria for excellence, while Mijen District is the non-basic area and the mainstay criteria. The relationship of various social, economic, and technical factors showed that the age of the breeder, the number of lactating cows, forage feed, and concentrate feed had a solid relationship (P<0.01) on milk production. While the experience of raising livestock, education level, and months of lactation did not have a significant relationship (P>0.05) on milk production. These results concluded that the two research areas still have the potential to be developed, and technical factors have an essential role in increasing milk production.